Epidemiological studies of traffic accident in the resort police of Sleman District, Yogyakarta 2015 – 2017 - Cahyaningtyas, Ayu; Wibowo, Trisno Agung (BKM Public Health and Community Medicine, 2021)
Objective: In 2010, the number of deaths caused by traffic accidents in Indonesia had reached 31.234 casualties (Lestari, 2012). In 2015, transportation accidents were the highest cause of death with 475 deaths out of 893 all cause deaths (53%). This research aims to determine the proportion and trends of traffic accidents and the relationship between the characteristics of casualties and the risk of deaths in traffic crashes. Method: This research was using observational analytic study design with cross sectional method. The research was conducted in Sleman District Police during April – June 2018. Samples of this research were all of the traffic accidents which collected secondary data from the police register during 2015-2017 in Sleman District Police. This research was using chi-square analysis. Result: There are a total of 3794 casualties from 2015-2017. Characteristic of the person which got the traffic accidents were male (76%), 15 – 24 years old (35%), have the drivers license (55%), entrepreneur (47%), upper secondary school (73%), ride the motorcycle (80%). Almost all the risk factor of the accidents was human factor (99%). Results of chi square analysis based on age : RP = 0.643 & p Value = 0.002, sex: RP = 1.504 & p Value = 0.027, type of vehicle: RP = 2,520 & p Value = 0.000, time of occurrence: RP = 0,741 & p Value = 0,046. Conclusion: Males and who used motorcycles were risk factors of traffic accidents in Sleman District. Supplying safe and comfortable public transportation can improve the used public transportation in the community, so it has reduced the incidence of traffic accidents.